The tumour and its microenvironment – a complicated interplay - Białas, Magdalena; Dyduch, Grzegorz; Adamek, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2011)
A whole range of complex interactions develops between growing malignant neoplastic cells and non-malignant stromal elements of a tumour. The tumour microenvironment includes a number of interrelated elements: fibroblasts, macrophages and dendritic cells, endothelial cells, pericytes, inflammatory cells and extracellular matrix components. All these elements are actively involved in tumour growth and progression and angiogenesis, and can either promote or inhibit these processes. Understanding of the relationship between the various components of the tumour microenvironment and tumour cells may allow the introduction of combination drug therapy having different target points which gives hope of reducing the doses of medicines, and thus reducing their toxicity while increasing their efficiency.